5PSQ-041 Efficacy and safety of cidofovir in the treatment of laryngeal papillomatosis: case reports. (March 2019) - Navarro, M; Puebla, A; Tevar, E; Mesa, R; Diaz, L; Ocaña, A; Viña, M; Plasencia, I; Gonzalez, I; Merino, J
Abstract : Background: Laryngeal papillomatosis is a larynx neoplasm due to the human papillomavirus virus (HPV) infection. It can appear during the first year of life, or during adulthood, which increases the probability of becoming malignant. It is characterised by tumours within the voice box, vocal cords or the air duct, causing dysphagia, stridor, sore throat or breathing problems. Surgery is the first-line treatment, but some patients require adjuvant treatment, such as cidofovir or alpha interferon. Purpose: To describe the efficacy and safety of the treatment with cidofovir in laryngeal papillomatosis. Material and methods: Five patients were diagnosed with laryngeal papillomatosis with a confirmed diagnosis by bronchoscopy and laboratory tests. In the general description of the study, the medical histories of diagnosed patients with recurrent respiratory papillomatosis treated in this institution from January 2014 to September 2019 were reviewed. They showed signs of inspiratory and expiratory stridor, tachypnea, elongated expiration with subcostal, suprasternal and intercostal retractions. Despite the interventions, the patients still maintained inspiratory and expiratory stridor so the treatment with alpha interferon was the next step. Results: According to the literature, treatment was started with a first-week dose of 12.5 mg/2 ml, followed by a dose of 12.5 mg/2 ml times per week. After the treatment three patients presented progression on their lesions and two other patients did not, with no lesions shown in their last control bronchoscopy. This permitted the extension of the frequency in the medical appointments from 1 to 2 months. A possible adverse effect associated was described, because of the appearance of dominant face erythematous lesions after the administration of some doses. All patients had mild nephrotoxicity. Conclusion: The results showed that cidofovir was neither an effective nor a relatively safe treatment for the treatment of laryngeal papillomatosis. However, these results cannot be considered as final outcomes, because the population of the study, just five patients, was too small. Although the evidence is insufficient for reliable conclusions, several series indicate that intralesional cidofovir may have some efficacy. A well-designed placebo-controlled, double-blinded, randomised and controlled trial will be required. References and/or acknowledgements: No conflict of interest.